Efektivitas Penerapan Model Pembelajaran Trade A Problem (T.A.P) Berbantuan Media Konkrit Untuk Meningkatkan Hasil Belajar Matematika Siswa di Kelas I SD Cordova Indonesia - Musfira Musfira (Concept: Journal of Social Humanities and Education, 2022)
This research aims to improve student learning outcomes in class I at SD Cordova Indonesia through the application of the trade a problem learning model assisted by concrete media. The problem in this research is the low mathematics ability of students in class I at SD Cordova Indonesia. The method used in this research is the classroom action research method (PTK). The subjects in this research were all 27 class I students at SD Cordova Indonesia. The indicator of success in implementing the action is that students achieve a minimum of 70% completeness with an average learning outcome score of at least 70 from the total number of students. Based on data processing from research results, the average value of student learning outcomes in the pre-cycle was 54.44, then after the first cycle actions were carried out it increased to 63.70. The first cycle action was then continued to the second cycle action and obtained an average score of 71.85 with student completion reaching 74.10% of the total students who took the learning outcomes test. Based on the results in cycle II, it shows that the application of the trade a problem learning model assisted by concrete media is effective in improving students' mathematics learning outcomes in class I at SD Cordova Indonesia.